2021
DOI: 10.1177/0310057x20972404
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low levels of patient satisfaction following peripheral nerve block

Abstract: Peripheral nerve blocks can provide surgical anaesthesia as well as excellent postoperative analgesia. When questioned postoperatively, however, some patients report low levels of satisfaction with their nerve block experience. At our hospital, patients undergoing regional anaesthesia have their patient characteristics, block characteristics and postoperative feedback routinely recorded in a block registry. We analysed data from 979 consecutive patients undergoing peripheral nerve block for orthopaedic surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…34,35 Because patients are less likely to be satisfied with a regional peripheral nerve block when they experience severe or moderate rebound pain, reducing the incidence of rebound pain is critical to patient satisfaction. 36 The risks of continuous catheters are similar to those of singleinjection nerve blocks but have their own unique concerns as well. Risks specific to prolonged infusions include the potential for delayed LAST, as peak plasma levels may not occur for 1 to 4 days after infusion due to accumulating doses of LAs.…”
Section: Continuous Catheter Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Because patients are less likely to be satisfied with a regional peripheral nerve block when they experience severe or moderate rebound pain, reducing the incidence of rebound pain is critical to patient satisfaction. 36 The risks of continuous catheters are similar to those of singleinjection nerve blocks but have their own unique concerns as well. Risks specific to prolonged infusions include the potential for delayed LAST, as peak plasma levels may not occur for 1 to 4 days after infusion due to accumulating doses of LAs.…”
Section: Continuous Catheter Techniquesmentioning
confidence: 99%
“…Finally, it has been reported that continuous catheters may reduce rebound pain 34,35 . Because patients are less likely to be satisfied with a regional peripheral nerve block when they experience severe or moderate rebound pain, reducing the incidence of rebound pain is critical to patient satisfaction 36 …”
Section: Continuous Catheter Techniquesmentioning
confidence: 99%
“…Peripheral nerve blocks (PNBs) using different techniques [ 1 ] are extensively used in orthopedic limb surgeries as they ease the surgical procedure and they improve patient satisfaction [ 2 ], particularly in terms of long-lasting postoperative analgesia without systemic drug side effects [ 1 ]. However, following PNB resolution, a rapid increase in pain intensity commonly referred to as “rebound pain” (RP) may occur.…”
Section: Introductionmentioning
confidence: 99%
“…The Anaesthesia and Intensive Care Jeanette Thirlwell Best Paper Award for 2021 has been awarded to Dr Anthony Hade and colleagues of the Department of Anaesthesia and Perioperative Medicine, Royal Brisbane and Women’s Hospital, Queensland, Australia, for their paper entitled ‘Factors associated with low levels of patient satisfaction following peripheral nerve block’. 1…”
mentioning
confidence: 99%
“…The Anaesthesia and Intensive Care Jeanette Thirlwell Best Paper Award for 2021 has been awarded to Dr Anthony Hade and colleagues of the Department of Anaesthesia and Perioperative Medicine, Royal Brisbane and Women's Hospital, Queensland, Australia, for their paper entitled 'Factors associated with low levels of patient satisfaction following peripheral nerve block'. 1 The 2021 Anaesthesia and Intensive Care Junior Investigator Award has been awarded to Dr Dilraj Thind of the Department of Anaesthesia and Intensive Care, Royal Papworth Hospital, Cambridge, UK, and the Department of Anaesthesia, Christchurch Hospital, New Zealand, for 'Coolsense V R versus EMLA V R for peripheral venous cannulation in adult volunteers: a randomised crossover trial'. 2 At a recent editors' meeting it was confirmed that this award will now be known as the Anaesthesia and Intensive Care Emerging Investigator Award.…”
mentioning
confidence: 99%